Cultural identity of waterfront community markets along Tha Chin River: A case study of Suphan Buri and Nakhon Pathom Provinces - Haocharoen, Kritaporn (Kasetsart Journal of Social Sciences, 2021)
The objective of this research was to study the general condition, structure, and cultural elements of waterfront community markets along Tha Chin River: A case study of Suphan Buri and Nakhon Pathom provinces. The study covered 24 waterfront community markets for both physical and non-physical characteristics. The results of the study indicate that Bang Luang Market is the waterfront community market that is most complete in cultural elements. Therefore, this market was selected for in-depth study at a specific area level. Additionally, the market has the most outstanding cultural structure, “community structure characteristics”, and the most striking cultural element, “the value of non-physical elements”, to promote physical elements (architecture) to be outstanding in quality. It can be concluded that the “socioeconomic characteristics” is the unique characteristics in remembrance of the market through the use of building and the reliance on the physical structure of the community. However, understanding the cultural identity of waterfront community markets should be the first mechanism or sustainable conservation and development planning.